2021
DOI: 10.1080/1331677x.2020.1865826
|View full text |Cite
|
Sign up to set email alerts
|

Market reactions for targets of M&A rumours—evidence from China

Abstract: This paper investigates investors' reactions to takeover rumours in China's stock markets from 2004 to 2014. While we find prerumour price run-ups (abnormal returns) for merger and acquisition (M&A) targets, the pre-rumour market overreaction is significantly positive only for target firms that are state-owned enterprises (SOEs). There are no significant abnormal returns for M&A rumour targets over a 41-day event window (À20, þ20). Nonetheless, capital market reactions to true rumours are higher than reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…They conclude that when CEOs are in positions of great power, the market reacts negatively because these CEOs exhibit overconfidence, making it easy to implement M&A deals incorrectly. By using cumulative abnormal return (CAR) to gauge market reaction in a rumors-heavy environment [ 21 ], provide evidence that the market reacts positively to real M&A news but reacts negatively to inaccurate rumors about M&A. In addition, a variety of other studies have suggested that the market reacts positively to the acquired company but negatively to the acquiring company, and almost all profits from operations mergers are accrued to the shareholders of the target company while the acquirer's shareholders receive zero or negative returns [ [22] , [23] , [24] ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They conclude that when CEOs are in positions of great power, the market reacts negatively because these CEOs exhibit overconfidence, making it easy to implement M&A deals incorrectly. By using cumulative abnormal return (CAR) to gauge market reaction in a rumors-heavy environment [ 21 ], provide evidence that the market reacts positively to real M&A news but reacts negatively to inaccurate rumors about M&A. In addition, a variety of other studies have suggested that the market reacts positively to the acquired company but negatively to the acquiring company, and almost all profits from operations mergers are accrued to the shareholders of the target company while the acquirer's shareholders receive zero or negative returns [ [22] , [23] , [24] ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Şirketlerin getiri verileri ve olay analizinde kullanılacak olan BIST-100 endeks getirisi ise investing.com adresinden elde edilmiştir. Şirketlerin duyuru tarihleri birleşme işlemine ait resmi tarihi belirtirken, dedikodu (söylenti) tarihleri ise şirket hakkında satın alma ve birleşmenin ilk olarak yönetim birimleri tarafından söylenmesi veya ülkenin bilinen gazetelerinde haber yapıldığı tarih olarak veri tabanına kaydedilmektedir (Yang and Chen, 2021). Analize konu olan şirketler alıcı şirket ve hedef şirket olarak Tablo 1'de gösterilmiştir.…”
Section: Ampirik Analiz Ve Veri Setiunclassified
“…The information could be primary data, such as results from an interview or survey, or it could be secondary data, such as an income statement or other financial report from a listed or private corporation, or even comments in an investment forum [97]. Some market information has a longer life span, and some may be more accurate or relevant [98]. For effective market information to be selected, acquired, and used, establishing information acquisition networks in the target markets is an especially important part of the information acquisition process [99].…”
Section: Instrumentationmentioning
confidence: 99%